Cavity Beam Position Monitor for the ILC Main Linac: Status and Plans - Pedraza Laura Karina; Fuster Martínez Nuria; Esperante Pereira Daniel; Gimeno Martínez Benito; González Iglesias Daniel; Blanch Gutiérrez César (EPJ Web of Conferences)
This work describes the preliminary study and evaluation of the design of a cavity beam position monitor (cBPM) for the Main Linac at the International Linear Collider (ILC) project. It is required to design and build a prototype to be tested together with a superconducting quadrupole in a cryostat, with a spatial resolution of less than 1 micron. The design of a reentrant cBPM by CEA Saclay is used as the starting point for this analysis, where the geometry is evaluated to identify areas for improvement. A typical analog read-out system is simulated, allowing for a detailed evaluation of the impact of each component and providing opportunities to further estimate the device’s performance. Finally, the numerical BIR-ME 3D method is employed to estimate the cBPM output.